Analysis of the Effectiveness of Government Regulation Number 69 Of 1999 in Ensuring the Protection of Consumer Rights From the Sale of Food Products (Case Study: Pak Uwit Tanjung Jati Cracker Factory) - Tria Adhelia; Amru Syahputra Lubis (Fox Justi : Jurnal Ilmu Hukum, 2025)
This study examines the effectiveness of Government Regulation Number 69 of 1999 concerning Food Labels and Advertisements in protecting consumer rights, focusing on a case study of Pak Uwit Cracker Factory in Binjai City. This case is important to note because the products marketed do not include a halal label that can mislead consumers, especially those who are Muslim. The methodology used in this study is a normative legal approach, by examining the theory of legal effectiveness, consumer protection, and consumer rights. The results of the study indicate that although PP No. 69 of 1999 has regulated provisions regarding food labels normatively, its implementation in the field is still not optimal. The low level of supervision and lack of awareness among business actors regarding legal responsibility are inhibiting factors in consumer protection. Therefore, it is necessary to strengthen the supervision system and increase legal education for business actors, in order to create a fair, transparent trade climate that prioritizes consumer interests.